STRATEGI BUMDES MULYA JAYA DALAM PENGEMBANGAN WISATA PETUNG PARK DESA BELIK TRAWAS - Mega Tanti Ananta Mega; Hendra Sukmana (Journal Publicuho, 2025)
This research aims to analyse how the strategy of BUMDes Mulya Jaya in Petung Park Tourism Development in Belik Village, Trawas. To understand the social and economic aspects of BUMDes management in Belik Village, this research used a qualitative approach. Data was collected through purposive sampling and documented through observation, interviews, and documentation. Selection of informants using a purposive sampling method consisting of Belik village officials, BUMDes Mulya Jaya members (Chairman, Secretary, and Treasurer), and Petung Park tourists. Data analysis uses the model (Miles and Huberman 1992), which includes data collection, data reduction, data presentation, conclusion drawing and verification. The results of this study show that the first BUMDes Mulya Jaya strategy is to use promotion and marketing strategies by using digital marketing strategies through social media and working with content creators. In addition, physical banners are also used as a means of promotion. Second, the road accessibility strategy is still difficult because of the lack of community. Thirdly, tourism products are presented with typical culinary offerings with the unique idea of eating while playing water. And the last is the Human Resources strategy, managed professionally to maintain the sustainability of tourism. Some of these things make the BUMDes Mulya Jaya strategy in developing Petung Park Tourism, Belik Trawas Village, cannot be said to be successful overall.